2020
DOI: 10.1002/anie.202006020
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Partial Oxidation of Methane to Dimethyl Ether over Pt/Y2O3Catalysts Using an NO/O2Shuttle

Abstract: Using a mixture of NO + O2 as the oxidant enabled the direct selective oxidation of methane to dimethyl ether (DME) over Pt/Y2O3. The reaction was carried out in a fixed bed reactor at 0.1 MPa over a temperature range of 275–375 °C. During the activity tests, the only carbon‐containing products were DME and CO2. The DME productivity (μmol gcat−1 h−1) was comparable to oxygenate productivities reported in the literature for strong oxidants (N2O, H2O2, O3). The NO + O2 mixture formed NO2, which acted as the oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…During the tests carried out under these conditions and the mixture of CH 4 :NO:O 2 inert gas with a ratio of 20:1:1:78 and the catalyst in the amount of 0.3 g, it was possible to obtain DME in the amount of 110 µmol/(g•h). The low conversion of methane, at the level of 5%, resulted from the need to use an excess of it in order to prevent the formation of an explosive atmosphere in combination with oxygen [27,28] diagram below (Figure 3) shows the likely steps in the oxidation of methane to DME on the catalyst's surface.…”
Section: Synthesis Of Dimethyl Ether From Methanementioning
confidence: 99%
See 1 more Smart Citation
“…During the tests carried out under these conditions and the mixture of CH 4 :NO:O 2 inert gas with a ratio of 20:1:1:78 and the catalyst in the amount of 0.3 g, it was possible to obtain DME in the amount of 110 µmol/(g•h). The low conversion of methane, at the level of 5%, resulted from the need to use an excess of it in order to prevent the formation of an explosive atmosphere in combination with oxygen [27,28] diagram below (Figure 3) shows the likely steps in the oxidation of methane to DME on the catalyst's surface.…”
Section: Synthesis Of Dimethyl Ether From Methanementioning
confidence: 99%
“…Probable steps in the oxidation of methane to DME on the catalyst's surface. (a) Form of OCH 3-by the reaction of CH 3+ and NO2; (b) Formation of DME from the reaction of OCH CH 3+.Reproduced with copyright permission from[27]…”
mentioning
confidence: 99%
“…The results showed that NO was reduced to N 2 ; however, surface nitrate species were formed, considered key intermediate species for selective oxidation. [215] At the same time, Kye et al used CO as a promotor to improve the catalytic activity of Pt/CeO 2 over CH 4 activation and its conversion into methanol with a selectivity of over 95% at 300 °C. The performance of Pt/CeO 2 was attributed to active lattice oxygen produced at the Pt/CeO 2 interface, which enables selective reaction routes for converting CH 4 to methanol.…”
Section: Pt-based Catalystsmentioning
confidence: 99%
“…The results showed that NO was reduced to N 2 ; however, surface nitrate species were formed, considered key intermediate species for selective oxidation. [ 215 ] At the same time, Kye et al. used CO as a promotor to improve the catalytic activity of Pt/CeO 2 over CH 4 activation and its conversion into methanol with a selectivity of over 95% at 300 °C.…”
Section: Thermocatalytic Activation Of Methanementioning
confidence: 99%
“…This scheme is commonly proposed for the recycling of SO 3 in methyl bisulfate systems as mentioned previously, and more recently a catalytic system for the conversion of methane to DME with NO 2 produced in the couple gas phase reaction of NO and O 2 . [24] In both cases, it is crucial that the recycling scheme does not pose complicated gas separation with burdensome energy duties or substantial purges of the valuable feedstocks. Overall, these approaches that indirectly use O 2 as the final oxidant are conceptually interesting, yet their practicality relies on the ultimate ability to address these process-oriented issues.…”
Section: Viable Oxidantsmentioning
confidence: 99%